Innovative Approaches to Neuraxial Blockade in Children: The Introduction of Epidural Nerve Root Stimulation and Ultrasound Guidance for Epidural Catheter Placement - Ban CH Tsui (Pain Research and Management)
Continuous epidural blockade remains the cornerstone of pediatric regional anesthesia. However, the risk of catastrophic trauma to the spinal cord when inserting direct thoracic and high lumbar epidural needles in anesthetized or heavily sedated pediatric patients is a concern. To reduce this risk, research has focused on low lumbar or caudal blocks (ie, avoiding the spinal cord) and threading catheters from distal puncture sites in a cephalad direction. However, with conventional epidural techniques, including loss-of-resistance for localization of the needle, optimal catheter tip placement is difficult to assess because considerable distances are required during threading. Novel approaches include electrical epidural stimulation for physiological confirmation and segmental localization of epidural catheters, and ultrasound guidance for assessing related neuroanatomy and real-time observation of the needle puncture and, potentially, catheter advancement. The present article provides a brief and focused review of these two advances, and outlines recent clinical experiences relevant to pediatric epidural anesthesia.